Optimization and Feasibility Analysis of Satellite Earth Station Power System Using Homer - Hanaa T. El-Madany; Faten H. Fahmy; Ninet M. A. El-Rahman; Hassen T. Dorrah (Universitas Ahmad Dahlan, 2012)
Satellite earth stations which located in remote areas are one of many applications powered by the renewable energy sources. Ground system consists of ground station and control centers working together to support the spacecraft and the data user. Earth station consists of major subsystems, transmitter, receiver, antenna, tracking equipment, terrestrial interface equipment and power supply. Power subsystem is an important part that required for supplying the earth station with electrical power to continue communicating with its remote sensing satellite. This paper deals with simulation and optimal sizing of earth station power system using HOMER software. A combination of two energy sources (solar, and wind) to provide a continuous electric power production is used to determine the optimum system operation. Three system configurations are compared with respect to the total net present cost (NPC) and levelized cost of energy (COE). Also, economical study will be analyzed for energy demand and sensitivity analysis will be performed.